Utility of Insulinoma-Associated Protein 1 (INSM1) and Mucin 2 (MUC2) Immunohistochemistry in the Distinction of Endocrine Mucin-Producing Sweat Gland Carcinoma From Morphologic Mimics. (February 2022) - Quattrochi, Brian; Russell-Goldman, Eleanor
Abstract : Abstract: Endocrine mucin-producing sweat gland carcinoma (EMPSGC) is a rare low-grade adnexal malignancy with a predilection for the eyelids of elderly White women, which is associated with invasive mucinous carcinoma with endocrine features in one-third of cases. EMPSGC is characterized by the presence of neuroendocrine differentiation and mucin production. However, EMPSGC displays a variety of architectural patterns including solid, cribriform, papillary, and cystic growth. In addition, EMPSGC may also display nonendocrine cytologic features, such as apocrine change. Because of their variable appearance, EMPSGC can show significant morphologic overlap with certain histologic mimics, namely basal cell carcinoma, hidrocystoma, apocrine hidradenoma, and tubular adenoma. In addition, the often limited sampling of this anatomically delicate area can make the diagnosis of EMPSGC challenging. EMPSGC expresses neuroendocrine markers, including synaptophysin and chromogranin, often in a focal distribution. However, insulinoma-associated protein 1 (INSM1) has been found to be a more sensitive marker for EMPSGC. Recent studies have also demonstrated the expression of the gel-forming mucin 2 (MUC2) in EMPSGC, possibly signifying a lacrimal or conjunctival origin of these neoplasms. In this article, we discuss EMPSGC in the context of its histologic mimics (BCC, hidrocystoma, apocrine hidradenoma, and tubular adenoma) and we investigate the utility of the immunohistochemical expression of INSM1 and MUC2 in the distinction of EMPSGC from them. We demonstrate that INSM1 and MUC2 can reliably distinguish EMPSGC from these histologic mimics.